1996
DOI: 10.1007/bf00212376
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and estimating concentrations of polychlorinated biphenyls, dioxins, and furans in cattle milk and soils of Rhine-Delta floodplains

Abstract: In the Rhine-Delta, accumulation of microcontaminants in floodplain foodwebs has received little attention in comparison with aquatic communities. Here, soil and cattle milk samples were taken from three floodplains and analyzed for polychlorinated biphenyls (PCBs), dibenzodioxins (PCDDs) and dibenzofurans (PCDFs). Based on 2,3,7, 8-tetrachlorodibenzodioxin equivalents, total PCDD and PCDF residues in milk did not exceed the quality standard of 0.006 microg/kg fat weight. This was still the case if non- and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Thus, the study showed a very low contamination level of the long-life half-skimmed drinking milk far below the target value of 1 pg TEQ/g of fat. The observed results were of the same order of magnitude as results published in the literature for other countries (for example Germany (Blüthgen et al 1996;Hipplein et al 1996), UK [MAFF Food Surveillance Information Sheets, various years 100 (January 1997), 107 (June 1997), 120 and 123 (August 1997), 133 and 134 (November 1997), 136 (December 1997, 143 (March 1998)], Finland [Hallikainen and Vartiainen 1998), or Netherlands (Hendriks et al 1996)]. …”
Section: Foodsupporting
confidence: 76%
“…Thus, the study showed a very low contamination level of the long-life half-skimmed drinking milk far below the target value of 1 pg TEQ/g of fat. The observed results were of the same order of magnitude as results published in the literature for other countries (for example Germany (Blüthgen et al 1996;Hipplein et al 1996), UK [MAFF Food Surveillance Information Sheets, various years 100 (January 1997), 107 (June 1997), 120 and 123 (August 1997), 133 and 134 (November 1997), 136 (December 1997, 143 (March 1998)], Finland [Hallikainen and Vartiainen 1998), or Netherlands (Hendriks et al 1996)]. …”
Section: Foodsupporting
confidence: 76%
“…Accumulation in cattle was predicted to be somewhat higher if intake from soil is taken into account. About 2 to 30% of the dry matter ingested by vertebrates may consist of soil, with a value of 5% for cattle [64,70]. At 20% organic matter in floodplain soils, one may calculate that about 1% of the non‐mineral matter taken in by cows consists of dead organic solids.…”
Section: Resultsmentioning
confidence: 99%
“…This study only focused on certain POPs and exposure scenarios and did not consider additional routes of exposure (dietary intake) or special vulnerable populations with specific exposure scenarios [ 49 ]. However, in agricultural areas it must be considered that concentrations of additional contaminants (especially formerly used or emerging pesticides [ 50 , 51 ], polychlorinated dibenzo-p-dioxins and dibenzofurans [ 52 ], heavy metals [ 3 , 53 ], or other micropollutants [ 54 , 55 ]) may also contribute to a higher probability of adverse effects. Likewise, health risks may be underestimated owing to the nature of the simple additive model avoiding all compound interactions and their synergic effects.…”
Section: Discussionmentioning
confidence: 99%
“…According to the intensive farming in the floodplains and potential pathways for POP transfer to the human food chain, dietary exposure is expected to significantly contribute to HHRs. Various studies have provided strong evidence that the flooding of pastureland can indeed result in elevated concentrations of POPs in milk and meat produced on flood-prone land [ 52 , 56 , 57 ]. POPs are adsorbed on soil organic matter or in the plant rhizosphere so strongly that they are marginally transported to plant tissues [ 58 ].…”
Section: Discussionmentioning
confidence: 99%